Aborsi dalam Perspektif Agama-agama Samawi - Tien Rohmatin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2002)
This paper discusses abortion, the reasons behind its practice, and the perspectives of the Abrahamic religions on this issue. Fundamentally, all Abrahamic faiths prohibit abortion, viewing it as an inhumane act that destroys and terminates the life of a fetus, a potential human being that deserves respect and protection, even if conceived under unlawful circumstances. However, abortion is permitted in cases where the mother’s life is at risk. If pregnancy endangers the mother’s survival, abortion is allowed, and no legal or religious punishment is applied. Therefore, abortion cannot be legalized without compelling justification, as its legalization could encourage extramarital sexual relations.